Understanding the Discourses of Traumatic Birth and the Transition to Motherhood Using Relational Dialectics Theory - (:unkn) unknown (My University, 2018)
The majority of existing research regarding birth and the transition to motherhood focuses on the physical health outcomes of mother and baby, often ignoring the social and emotional impact of the birth process (Leggett, 2014). The lack of focus on social and emotional outcomes for new mothers may be especially harmful for those who experience traumatic birth, as it is subjective in nature and is often overlooked as a routine birth by health professionals (Alder, Stadlmayr, Tschudin, & Bitzer, 2006; Beck, 2004a). Traumatic childbirth is defined as an event occurring during the labor and delivery process that involves actual or threatened serious injury or death to the mother or her infant (Beck, 2004a). Framed by relational dialectics theory (Baxter, 2011), the current investigation sought to understand women’s meaning making processes in publicly shared stories about birth trauma and transition to motherhood. Contrapuntal analysis (Baxter, 2011) was used to identify culturally dominant systems of meaning embedded in women’s talk about traumatic birth and their transition to motherhood. Forty-one women’s stories recounting traumatic births were analyzed within a variety of contexts (e.g., natural birth, cesarean, preemie). The dominant discourse of intensive motherhood informed much of women's talk about pregnancy, traumatic birth, and transition to motherhood. Discursive interplay was also identified during pregnancy, birth, and motherhood communication through the struggle between the discourse of intensive motherhood and the discourse of individualism through negating, countering, and entertaining. Mothers only distanced themselves from the discourse of intensive motherhood when they spoke about their traumatic birth on an individual level, outside their role as mother, as women were largely supported intensive motherhood.
Keywords: contrapuntal analysis; relational dialectics theory; transition to motherhood; traumatic birth